Ontology and Evolution of Tiandao: A Comparative Study with Natural Law - Feifei Yan (Sinolingua: Journal of Chinese Studies, 2026)
The concept of "Tiandao" (The Way of Heaven) represents the ontological foundation of traditional Chinese philosophy, serving as the ultimate source of both cosmic order and human morality. This study deconstructs the five-fold connotations of Tiandao and synthesizes them with a comparative analysis of Western "Natural Law" to explore how these systems bridge the "is-ought" gap. Utilizing philological analysis, historical hermeneutics, and comparative methodology, the research examines classical texts from the Pre-Qin period to the Qing Dynasty Alongside Western traditions ranging from Stoicism to Enlightenment Rationalism. The analysis reveals that Tiandao evolved from a personified divine will into a naturalistic, cyclical, and moralized ontological system. Comparative results indicate that while Western Natural Law emphasizes rational rights, Tiandao prioritizes organic harmony. The dialectic between "Heavenly Order" and "Human Agency" reflects a unique holistic spirit, suggesting that modern global ethics can benefit from the integration of these two traditions. Ultimately, Tiandao remains a vital framework for understanding human responsibility within a self-regulating cosmos, providing a metaphysical anchor for contemporary ecological and social governance and offering a necessary corrective to the disenchantment of nature in modern industrial societies.